Immobilization of Candida antarctica lipase B on Polystyrene Nanoparticles - Miletic, Nemanja; Abetz, Volker; Ebert, Katrin; Loos, Katja (Macromolecular Rapid Communications, 2010)
Polystyrene (PS) nanoparticles were prepared via a nanoprecipitation process. The influence of the pH of the buffer solution used during the immobilization process on the loading of Candida antarctica lipase B (Cal-B) and on the hydrolytic activity (hydrolysis of p-nitrophenyl acetate) of the immobilized Cal-B was studied. The pH of the buffer solution has no influence on enzyme loading, while immobilized enzyme activity is very dependent on the pH of adsorption. Cal-B immobilized on PS nanoparticles in buffer solution pH 6.8 performed higher hydrolytic activity than crude enzyme powder and Novozyme 435. Published